The First Cranial Trepanation Find in a Meotian Burial Ground (Starokorsunskiy Settlement No. 2, Krasnodar Region) - Nataliya Ya. Berezina; Aleksandra N. Abramova; Artem K. Avakyan; Aleksei V. Ivanov; Inna L. Marmer; Evgeny Yu. Girya (Нижневолжский археологический вестник)
A young woman’s skeleton dating back to the Meotian archaeological culture was studied during the investigation of the paleoanthropological series of the burial ground of the Starokorsunsky settlement No. 2. The burial ground is located in the Krasnodar Territory and is dated to the 4th century BC – 2nd century AD, while the burial under discussion dates back to the 2nd century BC – 2nd century AD. A trepanation hole with signs of healing was found on the skull of a young female of 17–25 years of age. In order to describe the pathological changes recorded on the cranial vault recommendations applied in modern paleoanthropology were used. Differential diagnosis was performed using descriptive macroscopic and X-ray diagnostic methods. It was possible to establish that the trepanation hole was made at least several years before the death of the individual. We suggested that the reason for the operation could be early synostosis of the skull sutures, and this manipulation was designed to reduce intracranial pressure and headaches caused by it. The article discusses the likely origins of medical skills for surgical manipulation. It is concluded that so far the data obtained do not allow us to speak unequivocally about the acquisition of medical knowledge by Meots from residents of the Asian Bosporus or from the Sarmatian environment.